Current drug use and lack of HIV virologic suppression: point-of-care urine drug screen versus self-report - Qian, Han-Zhu (BioMed Central, 2014)
BACKGROUND: There have been inconsistent findings on the association between current drug use and HIV disease progression and virologic suppression. Drug use was often measured using self-report of historical use. Objective measurement of current drug use is preferred. METHODS: In this cross-sectional study, we assessed drug use through Computer-Assisted Self Interviews (CASI) and point-of-care urine drug screen (UDS) among 225 HIV-infected patients, and evaluated the association between current drug use and virologic suppression. RESULTS: About half (54%) of participants had a positive UDS, with a lower self-reported rate by CASI (42%) (Kappa score = 0.59). By UDS, 36.0% were positive for marijuana, 25.8% for cocaine, 7.6% for opiates, and 2.2% for methamphetamine or amphetamine. Factors associated with virologic suppression (plasma HIV RNA <50 copies/mL) were Caucasian race (P = 0.03), higher CD4 count (P < 0.01), current use of antiretroviral therapy (ART) (P < 0.01), and a negative UDS (P < 0.01). Among 178 current ART users, a positive UDS remained significantly associated with lower likelihood of virologic suppression (P = 0.04). CONCLUSIONS: UDS had good agreement with CASI in detecting frequently used drugs such as marijuana and cocaine. UDS at routine clinic visits may provide “real-time” prognostic information to optimize management.